2016
DOI: 10.20546/ijcrar.2016.409.006
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Study for Chemical Composition of Al-Ahdaab Field Crude Oil

Abstract: This research included determination of chemical composition of al-ahdaab crude oil (kute-Iraq) using liquidsolid chromatography method. The current study involved separation the components of crude oil by column chromatography was packing with alumina (AL 2 O 3) as a stationary-phases and several solvent as a mobile phase. The results of crude oil fractionations were 17.01% Asphaltene, 82.99% Maltene, which separated to Paraffinic (saturated) 44.11%, Aromatic 30.11% and Resin 4.20%. Crude oil fractionations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…To establish the reliability of the construct, the Cronbach alpha coefficient, the composite reliability, and the Dijkstra-Henseler's indicator (RhoA) must all be higher than 0.7 (Hair et al, 2017). To establish convergent validity, these values must be greater than 0.5 (Fornell & Larcker, 1981). Furthermore, a heterotrait-monotrait (HTMT) correlation ratio below 1 proves discriminant validity (Henseler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To establish the reliability of the construct, the Cronbach alpha coefficient, the composite reliability, and the Dijkstra-Henseler's indicator (RhoA) must all be higher than 0.7 (Hair et al, 2017). To establish convergent validity, these values must be greater than 0.5 (Fornell & Larcker, 1981). Furthermore, a heterotrait-monotrait (HTMT) correlation ratio below 1 proves discriminant validity (Henseler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…What's more, all the constructs' composite reliability are larger than the minimum threshold of 0.7. According to Fornell and Larcker (1981), under the circumstances, items of each construct were internally reliable and consistent. Finally, AVE values were higher than the threshold value of 0.50, which indicated at least 51.35% of the variance observed in the items could be accounted for by their hypothesized constructs (Fornell and Larcker, 1981).…”
Section: Measurement Model Estimationmentioning
confidence: 99%
“…Thus, the validity of convergents is indicated for all latent variables. (Arbuckle, 2016) (Anderson & Gerbing, 1988)(Claes Fornell and David F. Larcker, 1981) (Cacioppo, J. & Feng Kao, 1984) (Bors et al, 2006) (Hair et al, 2010) (Ghozali, 2017) Discriminant validity is shown when variance with correlation between latent variable pairs is lower than AVE for each variable.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%